PERFORMANCE EVALUATION OF IIB DARMAJAYA ACADEMIC INFORMATION SYSTEM USING COBIT 5.0 FRAMEWORK ON STUDENT SATISFACTION - Hakim, Lukmanul; Nugroho, Agung; Ma'ruf, M. Hasan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The academic information system (SIAKAD) really helps universities in processing data on student grades, courses, data on teaching staff (lecturers) and faculty/department administration which is still manual to be done with a computerized system. Thus, it is necessary to evaluate SIAKAD's performance so that we can find out the quality of the services that have been provided to students. This research requires a governance framework in the form of Control Objective for Information and Related Technology 5 (COBIT 5.0) which can provide benefits for an agency in achieving strategic goals and optimizing information technology services. Therefore, this research aims to see how the performance SIAKAD regarding satisfaction with IIB Darmajaya students and providing recommendations for improving the quality of student services. The method used in this research is a descriptive method with a quantitative approach. The evaluation results show that SIAKAD's maturity level is still low, there is a fairly large GAP between the current service maturity level and the expected performance level. The GAP in the APO.07 domain is 2.24, in the DSS.03 domain it is 2.23, in the DSS.04 domain it is 2.29, in the DSS.05 domain it is 2.18 and in the MEA.01 domain it is 2.40 . The average GAP for the entire domain is 2.27 and places the service quality of SIAKAD IIB Darmajaya in the Manage quality and needs to be strengthened to improve the quality of student services. The recommendation given is to provide easy access to student data and provide access for parents/guardians of students at SIAKAD.